2006
DOI: 10.1080/02643290600625749
|View full text |Cite
|
Sign up to set email alerts
|

Misperception in sentences but not in words: Speech perception and the phonological buffer

Abstract: We report two case studies of aphasic patients with a working-memory impairment due to reduced storage in the phonological buffer. The two patients display excellent performance in phonological discrimination tasks as long as the tasks do not involve a memory load. We then show that their performance drops when they have to maintain fine-grained phonological information for sentence comprehension: They are impaired at mispronunciation detection and at comprehending sentences involving minimal word pairs. We ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 61 publications
0
12
0
1
Order By: Relevance
“…Furthermore, comprehension difficulty was exacerbated for complex sentences. Jacquemot et al (2006) claimed to have found patients with a specific STM impairment, yet those same patients also exhibited difficulty in language comprehension tasks and sentence repetition tasks, resulting in phonological paraphasias. A truly pure deficit has proven quite elusive (though see Martin and Breedin, 1992).…”
Section: Challenges For Limited Emergencementioning
confidence: 99%
“…Furthermore, comprehension difficulty was exacerbated for complex sentences. Jacquemot et al (2006) claimed to have found patients with a specific STM impairment, yet those same patients also exhibited difficulty in language comprehension tasks and sentence repetition tasks, resulting in phonological paraphasias. A truly pure deficit has proven quite elusive (though see Martin and Breedin, 1992).…”
Section: Challenges For Limited Emergencementioning
confidence: 99%
“…Only a few had addressed the impact of cognitive load on speech processing, and rather indirectly (e.g., Jacquemot, Dupoux, Decouche, & Bachoud-Lévi, 2006;Mirman, McClelland, Holt, & Magnuson, 2008; see also Astheimer & Sanders, 2009). In Mattys et al's (2009) study, severe energetic masking decreased reliance on lexical-semantic knowledge and increased reliance on acoustic detail-namely, on acoustic cues linked to coarticulation.…”
Section: Methodsmentioning
confidence: 99%
“…Verbal working memory (vWM) involves both holding and manipulating speech-specific content so that it can be accessed by higher-order cognitive functions 3 . These can include, but are not limited to, operations necessary to support language such as syntactic/semantic operations 4 7 , and vocabulary acquisition during development 2 , 8 . Patients with vWM impairments can have difficulty with syntactic operations that involve maintaining verbal items in vWM until they can be resolved.…”
Section: Introductionmentioning
confidence: 99%